2022
DOI: 10.1002/mus.27481
|View full text |Cite
|
Sign up to set email alerts
|

Opinions on Pneumocystis jirovecii prophylaxis in autoimmune neuromuscular disorders

Abstract: Pneumocystis jirovecii (PJ) is ubiquitously present in the environment and capable of causing an interstitial pneumonia in immunocompromised subjects. It has been advocated that routine prophylaxis against PJ be given to patients with autoimmune neuromuscular conditions that require prolonged use of corticosteroid therapy and/or other immunosuppressive agents. Available data, however, suggest that the risk of PJ infection in patients with autoimmune neuromuscular diseases is extremely low and the widespread us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(157 reference statements)
0
4
0
Order By: Relevance
“…In fact, several recent articles analyzing the risk of infection and PJP in neuromuscular patients suggest a very low risk, questioning the need for routine PJP prophylaxis in neuromuscular patients. 4,27,28 Therefore, there may be skepticism as to the validity and applicability of infectious disease recommendations to neuromuscular practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several recent articles analyzing the risk of infection and PJP in neuromuscular patients suggest a very low risk, questioning the need for routine PJP prophylaxis in neuromuscular patients. 4,27,28 Therefore, there may be skepticism as to the validity and applicability of infectious disease recommendations to neuromuscular practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, this literature does not address neurological or neuromuscular patients specifically, does not present data from randomized‐controlled trials or other high‐quality sources, and does not represent consensus guidelines through a formal process (such as Delphi). In fact, several recent articles analyzing the risk of infection and PJP in neuromuscular patients suggest a very low risk, questioning the need for routine PJP prophylaxis in neuromuscular patients 4,27,28 . Therefore, there may be skepticism as to the validity and applicability of infectious disease recommendations to neuromuscular practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the daily dose and duration of glucocorticoid used in patients predisposing to PJP remain unknown. Some report [29] showed that steroid doses are insu cient for PJP risk strati cation and identi cation of prophylactic needs in autoimmune neuromuscular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term immunosuppression is a risk factor for Pneumocystis jirovecii pneumonia (PJP), although the risk of PJP specifically in patients with IMNM is not well known. We generally follow the guidelines for patients with autoimmune neuromuscular diseases and prescribe PJP prophylaxis in patients who are on long‐term high‐dose corticosteroids or corticosteroids with other immunosuppressive agents and additionally have comorbidities that increase the risk of PJP (e.g., active cancer, lymphopenia, low CD4 count, interstitial lung disease, severe organ dysfunction) 46 . Trimethoprim‐sulfamethoxazole is prescribed 160–80 mg daily or double strength three times a week.…”
Section: Considerations For Patients On Long‐term Immunosuppressionmentioning
confidence: 99%